System analysis of mathematical models of placement of transport and logistics facilities of different levels - O. V. Moskvichev; E. E. Moskvicheva (Вестник Научно-исследовательского института железнодорожного транспорта, 2022)
Introduction. The formation of an overarching network of nodal freight multimodal transport and logistics centres in the Russian Federation and organisation of high-speed freight traffic on schedule on its basis requires the development of science-based proposals for the creation or modernisation of the corresponding regional transport and logistics infrastructure. One of the most important tasks in the implementation of this project in the context of limited investment resources is the correct justification of the number and choice of locations for the transport and logistics centres of the overarching network in the Russian Federation, as well as the locations of transport and logistics centres in the constituent entities of the Russian Federation.Materials and methods. This article provides an evaluation analysis of the classical methods for finding optimal centres on a plane and some construction of mathematical quantitative models for the optimal placement of transport and logistics facilities.Results. According to the evaluation analysis, the authors have drafted a scientifically based concept of a systematic approach to the issues of rational design and placement of elements of transport and logistics infrastructure, in particular, the overarching network of nodal freight multimodal transport and logistics centres, as part of a new highly efficient transport and logistics infrastructure of the Russian Federation and its international transport corridors.Discussion and conclusion. The obtained results of the study can be used for scientifically based decision-making in investment projects related to the development of transport and logistics infrastructure at both regional and federal levels: substantiation of locations and technological capacities of transport and logistics infrastructure facilities; determining the need for the development of objects of the regional transport and logistics infrastructure, while eliminating their bottlenecks; implementation of a phased set of measures to modernise the existing terminal and logistics complex.